MANAGING SAFETY: THE ROLE OF SAFETY PERCEPTIONS APPROACH TO IMPROVE IN ORGANIZATIONS - Abdullah, Nor Azimah Chew; Spickett, Jeffery T.; Rumchev, Krassi B.; Dhaliwal, Satvinder S.; Goh, Yang Miang (International Business Education Journal, 2009)
This study was carried out to investigate current practices and attitudes towards the management of Occupational Health and Safety (OHS) in a public hospital in northern region of Malaysia. Data were collected using a set of questionnaires. Data analysis was done using descriptive statistics, Pearson correlation and multiple regressions. Empirical evidence indicated that there were no differences in safety reporting, safety satisfaction, errors and incidents, safety rules, safety communication, training & competence, work pressure, management commitment, roles of supervisor and leadership style faced by the male and female workers. In addition, the results also showed that there were no significant difference for seven variables such as safety reporting, errors and incidents, safety rules, safety communications training & competence, work pressure, and management commitment but there were significant effects for three variables: safety satisfaction, roles of supervisor, and leadership style among the respondents with four types of education level. The findings suggested that there was a significant positive correlation between safety satisfaction and seven elements of OHS management namely safety reporting, errors and incidents, management commitment, work pressure, role of supervisor, safety rules, and leadership style. The regression analysis revealed approximately 54.8% (R2 = 0.548) of variance in safety satisfaction that was explained by the nine independent variables. In conclusion, the results highlighted an important finding: the employees perceived that there was a need to improve the workplace by perceived that there was a need to improve the workplace by emphasizing all the OHS management practices as significant in relation to safety.